Molecular Docking of Pomegranate Peel (Punica granatum L.) Active Compounds by Targeting Tumor Necrosis Factor Alpha (TNF-α) in Diabetes Condition - Yuniarto, Ari; Rangkuti, Saru Noliqo; Junaidin (MPI (Media Pharmaceutica Indonesiana), 2024)
Diabetes mellitus is a group of metabolic disorders characterized by increased blood glucose concentration, known as hyperglycemia. Several studies report that diabetes mellitus is associated with the presence of tumor necrosis factor-α (TNF-α). One of the medicinal plants that has the potential to be used to treat diabetes mellitus is pomegranate (Punica granatum L.). Therefore, this study aimed to observe the effect of bioactive compounds of pomegranate peel as antidiabetic against TNF-α using a molecular docking approach. The stages of molecular docking include geometry optimization, validation of the docking program, docking ligand test, and visualization of the docking results. The target compounds analyzed from pomegranate peel were ellagitannin and punicalagin. The macromolecular target wasTNF-α. Redocking between the original ligand and the target TNF-α showed an RMSD value of ≤ 2.0 Å with a value of 0.4902 Å. The hydrophobic interaction was formed between ellagitannin and punicalagin on the TNF-α target shows excellent ligand-receptor interactions, this can be seen from the binding free energy value which is smaller when compared to the co-crystal ligand. These results indicate that the complex formed from tethering ellagitannin and punicalagin to the TNF-α target is more stable than the original ligand complex with the TNF-α target. Based on the research results, it can be concluded that pomegranate peel has excellent potential as an antidiabetic. In silico research shows that pomegranate peel content such as ellagitannin can bind stably with TNF-α (ΔG = -132.44kcal/mol), so it is predicted to be able to suppress TNF-α which is responsible for the emergence of diabetes mellitus. Submitted: 05-10-2024, Revised: 16-11-2024, Accepted: 25-11-2024, Published regularly: December 2024